Stabilisation/solidification of lead-contaminated soil by using ladle furnace slag and carbon dioxide - Xu, Bo (2023)
Global sustainable development faces challenges in greenhouse gas emission, consumption of non-renewable resource and energy, waste landfilling, and environmental pollution. Geotechnical engineering also faces similar challenges; for example, the use of cement and lime for stabilisation/solidification (S/S) of contaminated soil is associated with carbon dioxide (CO2) emission and consumption of limestone and energy. In this context, this study introduces a sustainable S/S method by using an industrial waste, ladle furnace slag (LFS), and a greenhouse gas, CO2, to replace common additives for S/S of lead (Pb)-contaminated soil. LFS was first mixed with Pb-contaminated soils and then CO2 was introduced into the soil for carbonation. The results showed that LFS-stabilised Pb-contaminated soils could achieve CO2 uptake up to 18% of LFS mass. After carbonation, the concentration of leached Pb from contaminated soils was reduced by three orders of magnitude than that without carbonation, demonstrating higher S/S efficacy than cement, lime, and magnesia. Additionally, this method can improve soil strength, as well as reduce non-renewable resource consumption, energy use, LFS landfilling, and additive cost.